Pentingnya Ketrampilan Berpikir Tingkat Tinggi (High Order Thinking Skills) Kaitannya dalam Menyelesaikan Soal Pemecahan Masalah Matematika - Tri Novita Irawati; Muhlisatul Mahmudah (FKIP Universitas Islam Jember, 2018)
This study aims to discuss the importance of High Order Thinking Skills in relation to solve mathematical problem solving. The method used is to describe the learning of mathematics related to problem solving using high-level thinking skills based on the results of a supportive reference study. Problem solving is a high-level mental process and requires a more complex process of thinking. Problem solving is a non-routine problem, meaning that the problem cannot be solved directly. This problem requires higher thinking skills in solving them. High Order Thinking Skills in Bloom Taxonomy in the cognitive domain consist of six levels: remembering, understanding, understanding, applying, analyzing, analyzing and evaluating (create). With high-level thinking skills a person will be able to solve problem solving problems properly. Given the importance of high-level thinking skills, these skills must be possessed by each student in answering mathematical problem solving. Keywords: High order thinking skills, problem solving questions